China's Multi-Stakeholder Engagement in Indonesia via Development-Driven Public Diplomacy - Riyanto, Budi; Amaliyah, Ridha; Nuraini, Rahmi (Global and Policy Journal of International Relations, 2025)
This paper examines China's "development-driven" public diplomacy in Indonesia, focusing on how economic initiatives, particularly under the Belt and Road Initiative (BRI), strategically engage the multi-stakeholder ecosystem comprising Academia, Business, Government, Community, and Media (ABGCM). Drawing on the Penta Helix framework, the study argues that China utilizes tangible development projects, such as Luban Workshops, the Jakarta-Bandung High-Speed Rail, and the Morowali Industrial Park, as deliberate platforms to shape Indonesian perceptions, strengthen bilateral ties, and advance its strategic goals. Analysis reveals that this multi-stakeholder engagement results in uneven effectiveness and inherent contradictions. While these initiatives often deliver discernible economic benefits and foster positive sentiment in certain quarters, particularly strengthening Government-to-Government (G-G) and Business-to-Business (B-B) ties, they simultaneously produce significant negative externalities, social friction, environmental degradation, and public skepticism. The effectiveness varies across cases and ABGCM pillars; Luban Workshops show positive outcomes with targeted groups. HSR and IMIP face substantial negative feedback from the Community, Media, and NGOs due to implementation issues and social/environmental costs. The study highlights those Indonesian stakeholders who actively mediate outcomes. It contributes a nuanced understanding of how development functions as a public diplomacy tool within a complex domestic context and the challenges of balancing economic objectives with achieving broad social acceptance and legitimacy.